Does HLA-B*27 subtypes and ethnicity matter in Ankylosing Spondylitis? - Sulaiman, Salsabil; Too, Chun Lai; Tan, Lay Kim Tan; Ahmad Fauzi, Nurul Aain; Hussein, Heselynn; Rajalingam, Shamala; Sularman, Wahinuddin; Ong, Ping Seung; Rosman, Azmillah; Mohd. Zain, Mollyza; Lau, Ing Soo; Gun, Suk Chyn; et al. (2017)
Ankylosing Spondylitis (AS) is a chronic, progressive inflammatory disorder that results in ankylosis of the vertebral column and sacroiliac joints.  More than 30% of patients with AS carry a heavy burden of disease and have a decreased quality of life.  The HLA-B*27 is a well known genetic risk variant for ankylosing spondylitis (AS).  However, the degree of association varies for different subtypes and depends on ethnicity.  Malaysia is a multi-ethnic country comprises Malays as the largest ethnic group, followed by Chinese, Indians and mixed-ethnicities.